2017
DOI: 10.1016/j.kint.2017.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte-specific JAK2 overexpression worsens diabetic kidney disease in mice

Abstract: Activation of the JAK-STAT signaling has been implicated in the pathogenesis of diabetic kidney disease. An increased expression of JAK-STAT genes was found in kidney glomerular cells, including podocytes, in patients with early diabetic kidney disease. However, it is not known whether increased expression of JAK or STAT isoforms in glomerular cells can lead to worsening nephropathy in the setting of diabetes. Therefore, we overexpressed JAK2 mRNA specifically in glomerular podocytes of 129S6 mice to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 31 publications
0
61
0
Order By: Relevance
“…A pathogenic role for cytokine signaling in proteinuric diseases is supported by a recent publication describing a transgenic mouse overexpressing JAK2 in podocytes (48). When crossed with the Akita diabetic nephropathy mouse model infused with angiotensin II, enhanced proteinuria was observed that was largely reversed with JAK2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…A pathogenic role for cytokine signaling in proteinuric diseases is supported by a recent publication describing a transgenic mouse overexpressing JAK2 in podocytes (48). When crossed with the Akita diabetic nephropathy mouse model infused with angiotensin II, enhanced proteinuria was observed that was largely reversed with JAK2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Human glomerular MCs express NADPH oxidase and activates protein kinase C, mitogen activated protein kinase, and nuclear factor-jB (NF-jB) which eventually results in overproduction of extracellular matrix proteins [27]. Excess fibroblasts infiltrate the interstitium with consequent progressive interstitial fibrosis [28]. Hyperglycemia triggers increased intracellular fibroblast growth factor 23 (FGF23) is a phosphatonin responsible for renal phosphate elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, whole body GHR/ binding protein (BP) gene disruption protected mice against the development of DN [7]. Mice overexpressing JAK2, an immediate target of GH/GHR axis in podocytes resulted in thickening of GBM and foot process effacement [27]. Therefore, we hypothesized that targeted deletion of GHR in podocytes may prevents renal hypertrophy and proteinuria in experimental diabetic mice.…”
Section: Former One Suggests Autocrine and Later Suggest Paracrine Acmentioning
confidence: 99%